Assessment of Spaceflight Medical Conditions' and Treatments' Potential Impacts on Behavioral Health and Performance. (August 2021) - Roma, Peter G.; Schneiderman, Jason S.; Schorn, Julia M.; Whiting, Sara E.; Landon, Lauren Blackwell; Williams, Thomas J.
Abstract: Long-duration space exploration missions will pose significant risks to the physical and behavioral health and performance of the crew. We documented the presence and frequency of (1) behavioral health and performance (BHP)-relevant symptoms for each condition in NASA's Exploration Medical Conditions List (EMCL), (2) the BHP-relevant effects of applicable medical treatments in the current International Space Station (ISS) On-Orbit Medication List, (3) the breadth of potential BHP impacts of spaceflight medical treatments, and (4) the likelihood of adverse BHP effects of treating spaceflight medical conditions. BHP symptoms and effects were categorized by the six neurobehavioral domains of the National Institute of Mental Health's Research Domain Criteria (RDoC) framework. Including the cognitive effects of acute and chronic pain (e.g., attention, memory), 94% of spaceflight medical conditions include symptoms relevant to Cognitive Systems (e.g., attention deficits, confusion, psychosis), 36% include symptoms relevant to Negative Valence Systems (e.g., anxiety), 32% include symptoms relevant to Arousal and Regulatory Systems (e.g., sleep disturbances), 22% include symptoms relevant to Sensorimotor Systems (e.g., dizziness), 19% include symptoms relevant to Positive Valence Systems (e.g., mania), and 11% include symptoms relevant to Social Processes (e.g., social withdrawal). Only 2% of spaceflight medical conditions have no documented BHP symptoms. Of the spaceflight medical treatments, 63% affect Arousal and Regulatory Systems, 60% affect Sensorimotor Systems, 59% affect Cognitive Systems, 53% affect Negative Valence Systems, 38% affect Positive Valence Systems, and 31% affect Social Processes. The breadth of potential BHP impacts was bimodal, in that 27% of spaceflight medical treatments had no documented BHP effects; however, 27% of treatments may produce adverse effects across all six neurobehavioral domains. Historical prevalence data on medical conditions, symptoms, and complaints from 14 years of International Space Station operations coupled with documented BHP effects of recommended treatments indicates the potential for up to 481 adverse BHP effects of spaceflight medical treatments per person-year. Assessing the potential BHP impacts of spaceflight medical conditions and their treatments highlights the interactive nature of operational risks, and can provide an enhanced evidence base to support integrated research and countermeasure development strategies for long-duration exploration missions.